2003
DOI: 10.1046/j.1440-1746.2003.03191.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hepatoma‐derived growth factor in hepatocarcinogenesis

Abstract: The present findings suggest that HDGF plays an important role in the development or progression of HCC in humans and rodents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 42 publications
1
46
1
Order By: Relevance
“…Of the 57 specimens tested, 52 expressed higher levels of HDGF than adjacent noncancerous stomach tissue. This result suggests that the overexpression of HDGF is a frequent event in gastric cancer, which is consistent with results reported previously (10)(11)(12)(13). The relationship between HDGF expression and p53 mutational status was then investigated.…”
Section: Expression Of Hdgf and P53 Mutation In Human Cancer Tissuesupporting
confidence: 90%
See 2 more Smart Citations
“…Of the 57 specimens tested, 52 expressed higher levels of HDGF than adjacent noncancerous stomach tissue. This result suggests that the overexpression of HDGF is a frequent event in gastric cancer, which is consistent with results reported previously (10)(11)(12)(13). The relationship between HDGF expression and p53 mutational status was then investigated.…”
Section: Expression Of Hdgf and P53 Mutation In Human Cancer Tissuesupporting
confidence: 90%
“…Because HDGF possesses proliferative and angiogenic and activity (10,(30)(31)(32), the functional implication of HDGF in cancer cell growth was investigated. Colony formation assays revealed that the growth of HCT116 cells and HeLa cells was significantly enhanced in response to recombinant HDGF protein in a dose-dependent manner (Fig.…”
Section: Suppression Of Cancer Cell Growth By P53-mediated Repressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, HDGF is more abundantly expressed in HCC than in adjacent non-tumor liver tissues. 20) HDGF is a unique nuclear/growth factor, possibly playing an important role in the development and progression of cancer cells.…”
mentioning
confidence: 99%
“…It has been reported that HDGF participates in the development of liver cancer and gastric cancer (27,28). Overexpression of HDGF results in tumorigenesis by NIH 3T3 cells, and dowregulation of HDGF inhibits the tumorigenicity of NSCLC cells in vivo (10,20).…”
Section: Discussionmentioning
confidence: 99%